3√10 - 2(4√10 +3) + 5√10 =?
Răspunsuri la întrebare
Răspuns de
3
[tex]3 \sqrt{10}-2(4 \sqrt{10}+3)+5 \sqrt{10}= \\
3 \sqrt{10}-8 \sqrt{10}-6+5 \sqrt{10}= \boxed{-6}
[/tex]
mihalulus:
mersi :)
Răspuns de
1
3√10 - 8√10 - 6 + 5√10 = 8√10 - 8√10 - 6 = - 6 , dupa reducerea 8√10 cu - 8√10
Sper ca ti-am fost de ajutor!
Sper ca ti-am fost de ajutor!
Alte întrebări interesante
Matematică,
9 ani în urmă
Biologie,
9 ani în urmă
Matematică,
9 ani în urmă
Istorie,
9 ani în urmă
Matematică,
9 ani în urmă
Fizică,
10 ani în urmă